UPAYA PENINGKATAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN METODE STUDENT TEAM ACHIVEMENT DIVISION (STAD) PADA MATA PELAJARAN SENI BUDAYA TARI KELAS VII-6 SMPN 30 RUMBAI KECAMATAN RUMBAI PESISIR KOTA PEKANBARU PROVINSI RIAU - Erawati, Yahyar; AfriliaNasution, Fitri; Suryani, Nike (Perspektif, 2016)
The title of this research was “The Efforts in Improving Students’ Learning Outcome inCultural Arts Dance Subject by Using Student Team Achievement Division (STAD) Class VII6 SMP 30 Rumbai Kecamatan Rumbai Pesisir Kota Pekanbaru Provinsi Riau". Formulationof the problem was how to Increase Student Learning Outcomes Method Using Student TeamAchievement Division (STAS) at Subjects Cultural Arts Dance Class VII-6 SMP 30 RumbaiKecamatan Rumbai Pesisir Kota Pekanbaru Provinsi Riau. This research was a type of classaction research. Based on the data that has been analyzed and in the interpretation of data, itcan be concluded that the application of the method of STAD can improve students' skills inunderstanding the pattern of the dance floor as well as demonstrating a broken swing danceclass nine VII.6 SMP Negeri 30 Rumbai Kecamatan Rumbai Pesisir Kota Pekanbaru ProvinsiRiau school year 2014/2015. The data can be seen in the initial test before using STAD andafter using the learning method STAD first cycle and the second cycle which included theabsorption and mastery learning. Pada preliminary tests before using STAD gained 53.04%while the absorption of mastery learning 11.90% of students 5 out of the 42 students. Whenusing the learning method STAD first cycle absorption Values for quiz grades and brokenswing dance nine students rose to 64.78% and reached 33.33% completeness study that 14 of42 students. While absorption and mastery quiz on the second cycle increased to 73.30% and66.67% completeness that 28 of 42 students.